Managing Image in the Midst of Uncertainty: A Systematic Analysis of Destination Communication Strategies Post-Security Crisis - Dedy Iswanto; Sulhan Hadi; Baiq Reinelda Tri Yunarni; Muhammad Fuzail (Jurnal Ilmiah Manajemen & Bisnis, 2026)
Post-security crises, particularly those arising from political instability or natural disasters, tourism destinations in Indonesia face challenges in managing their image and sustaining tourist visits. Effective crisis communication strategies, including transparent actions and engagement with tourists, play a crucial role in rebuilding trust and loyalty, essential for long-term tourism sustainability. These strategies, along with smart tourism technologies and community involvement, are vital for managing destination image during and after a crisis, ensuring recovery and maintaining tourist interest. This study explores key strategies destinations use to manage their image post-crisis, focusing on the role of smart tourism technologies (STT) and content marketing in fostering tourist loyalty, and investigates community involvement in building resilience. A systematic literature review using the PRISMA framework was conducted, supplemented by bibliometric analysis with VOSviewer, covering 18 articles published between 2020 and 2025. Adaptive crisis communication, STT (AI, VR), content marketing, and community engagement are essential in restoring destination image and sustaining tourist loyalty. Digital platforms and UGC play significant roles in shaping visitor perceptions and decisions. The integration of digital strategies, transparent communication, and community involvement are crucial for post-crisis recovery and long-term resilience. Emotional engagement and perceived safety significantly influence the effectiveness of these strategies. This study provides unique insights into strategies for managing tourism destinations' post-crisis recovery. It offers practical guidance for managers on how to integrate crisis communication strategies, community involvement, and digital innovations to enhance both tourist loyalty and destination resilience, ensuring long-term sustainability.